Morpho-functional basis of endothelial dysfunction in diabetes mellitus - A. I. Gozhenko; H. S. Kuznetsova; K. S. Kuznetsova; O. M. Kuznetsova; T. M. Byts; W. Zukow (Journal of Education, Health and Sport, 2017)
The diabetes mellitus (DM) inevitably progresses and leads to complications, among which the main place is occupied by micro- and macroangiopathies. The presence of endothelial damage in DM can be established even before macroscopically significant damage to the vessel. At the same time, there is no summary ED characteristic for diabetes. The aim of the study is to make a comprehensive evaluation of ED in DM -1 and DM-2 types. Materials and methods of research. 60 persons, including 53 DM type 1 and type 2, with a severe course (state of decompensation) participated in the present study. We used the method of estimating ED by the number of circulating desquamation endothelial cells (CECs) at the stages of decomposition with simultaneous determination of NO2- and NO3- metabolites of nitric oxide.